2019
DOI: 10.1021/acsenergylett.8b02383
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Morphology Stability under Multiple Stresses in Organic Solar Cells

Abstract: Improving device stability is an imperative area of realizing commercial utilization for organic solar cells (OSCs). Morphology evolutions of solution-processable active layers have proved to be responsible for ubiquitous device degradation due to their profound impacts on charge generation, transport, and extraction. This Perspective aims to understand and promote device stability in terms of morphology control and evolution from the subnanoscale to hundreds of nanometers. We start with analyzing the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 50 publications
0
53
0
Order By: Relevance
“…Apart from the lifetime stability, the mechanical property is also an indispensable property for achieving flexible and large‐area OSCs. To improve that part, photoactive film nanostructure must remain stable over considerable time and adequate crystalline donor/acceptor features to resist mechanical stress . We have seen polymer/polymer blend films exhibiting excellent mechanical property for their obvious advantage of providing excellent inter‐chain network, forming a large plastic zone at the crack tip during the process of applying stress.…”
Section: Detailed Photovoltaic Parameters Of Blade‐coated Oscs Under mentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the lifetime stability, the mechanical property is also an indispensable property for achieving flexible and large‐area OSCs. To improve that part, photoactive film nanostructure must remain stable over considerable time and adequate crystalline donor/acceptor features to resist mechanical stress . We have seen polymer/polymer blend films exhibiting excellent mechanical property for their obvious advantage of providing excellent inter‐chain network, forming a large plastic zone at the crack tip during the process of applying stress.…”
Section: Detailed Photovoltaic Parameters Of Blade‐coated Oscs Under mentioning
confidence: 99%
“…The molecular weight information of PTB7‐Th and N2200 is shown in Figure S9, Supporting Information. Additionally, the mechanical property of the devices is also closely related to the morphology parameters, such as D/A interfaces and molecular order . The tensile parameters were measured to acquire a quantitative comparison of the mechanical property.…”
Section: Detailed Photovoltaic Parameters Of Blade‐coated Oscs Under mentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34][35][36] In addition, as the photovoltaic performance of OSCs highly depends on the blend film morphology, in-depth understanding of the relationship between morphology and photovoltaic performance of ternary OSCs is of great importance to further improve the development of OSCs. [37][38][39][40] Here, the photovoltaic performance and morphology evolution of a low-cost polymer donor PTQ10 that possess low-lying HOMO and the recently reported A-DA'D-A-type n-OS acceptor Y6 were carefully investigated. Although the HOMO energy offset of PTQ10 and Y6 is rather small, the device based on them could efficiently operate, thus efficient photovoltaic performance with high V oc and low energy loss was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[41,42] However, the intrinsic instability of active layer morphology driven by light, temperature, and thermodynamics cannot be prevented by encapsulation. [43] For instance, McGehee and co-workers [29] reported that solar cells based on amorphous materials would suffer from open-circuit voltage (V OC ) burnin degradation resulted from the impact of light-induced traps, and this degradation can be reduced by using materials with high degree of crystallinity. [43] For instance, McGehee and co-workers [29] reported that solar cells based on amorphous materials would suffer from open-circuit voltage (V OC ) burnin degradation resulted from the impact of light-induced traps, and this degradation can be reduced by using materials with high degree of crystallinity.…”
mentioning
confidence: 99%